STRUCTURE AND CYTOCHEMICAL FEATURES OF STIGMA AND STYLE OF ORNITHOGALUM SIGMOIDEUM FREYN&SINT, UNPOLLINATED AND POLLINATED PISTIL - (:unkn) unknown (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, PAS BRANCH CRACOW, 2012)
The stigma of Ornithogalum sigmoideum is of dry and papillate type. The papillae are covered by a cuticle-pellicle layer, as revealed by staining. The activity of nonspecific esterase, acid phosphatase and peroxidase increases in the pellicle during the receptivity period. The style of O. sigmoideum is of the hollow type. Ultrastructural study of the cells lining the canal indicated that they are secretory cells and contain abundant endoplasmic reticulum, dictyosomes, mitochondria, plastids and ribosomes. After anthesis these organdies show degeneration at the end of the secretory phase. In canal cells, cytochemical tests showed the presence of acidic polyanions, insoluble and acidic polysaccharides, proteins and lipids. Before anthesis the canal cells are rich in polysaccharides, proteins and lipids. At maturity the cuticle is ruptured and secretory materials from the canal cells are released Into the canal. In the unpollinated style of O. sigmoideum the exudates accumulated in the center of the canal: In pollinated pistils the same secretion materials were dispersed through the canal, which became wider.
Keywords: Ornithogalum sigmoideum; stigma; style; unpollinated style; pollinated style; cytochemistry; POLLEN-TUBE; LILIUM-LONGIFLORUM; RECEPTIVITY; PROTEINS; ACID; PAPILLAE; SURFACE; ROLES